The Cenomanian: stage of hindlimbed snakes - Rage Jean-Claude; Escuillié François (Carnets de Géologie, 2003)
Three "snakes with legs" are known: Pachyrhachis problematicus, Haasiophis terrasanctus and Eupodophis descouensi. They have short posterior limbs but lack an anterior girdle and forelimbs. Moreover, Pachyophis woodwardi, Mesophis nopcsai and Simoliophis ssp. appear to be closely related to the hindlimbed taxa; consequently, although the presence of posterior limbs has not been demonstrated for these genera, it is presumed that they too were hindlimbed. All these snakes have been recovered only from the Cenomanian. Moreover, these six genera come from a restricted area (western Europe and northwesternmost Africa to the Middle East). This limited geographic range suggests that snakes might have originated in the "Mediterranean" part of the Tethys, but the restricted stratigraphical range remains unexplained.